Single Crystal Growth and Structural Study of the New MCu2Zn20 (M = Nb, Hf) Compounds - Sarah M. Longworth; Marium M. Mou; Nusrat Yasmin; Md Fahel Bin Noor; Ridwan Sakidja; Tiglet Besara (Crystals)
Two new cage-structured compounds—NbCu2Zn20 and HfCu2Zn20—belonging to the MM’2X20 (M, M’ = transition or rare earth metals, and X = Al, Zn, or Cd) family of structures have been synthesized via the self-flux method. The new compounds crystallize in the space group <semantics>Fd<mover accent="true">3¯</mover>m</semantics> with lattice parameter 13.9013(2) Å for NbCu2Zn20 and 13.9856(2) Å for HfCu2Zn20. The structures follow the expected metallic radii trend in MM’20Zn20 (M = Nb or Hf, M’ = Mn, Fe, Co, Ni, and Cu). While NbCu2Zn20 is stoichiometric, HfCu2Zn20 exhibits Cu/Zn site mixing and Hf-site underoccupancy, resulting in a final stoichiometry of Hf0.96Cu1.67Zn20.33 (Hf1–δCu2–xZn20+x, δ = 0.04, x = 0.33).